A Low PAPR Universal Filtered Multi-Carrier System for 5G Machine Type Communications - Baig, I. (IEEE Computer Society, 2019)
Universal Filtered Multi-Carriers (UFMC) has become one of the favorable modulation systems for upcoming 5G Machine-Type Communications (MTC) communications due to its robustness against multiuser interference, fragmented spectrum suitability and short burst support. However, UFMC systems faces a challenging problem in the form of high Peak-to-Average Power Ratio (PAPR) at the transmitter side. The high PAPR value downplays the efficiency of UFMC transmitter. To counter the high PAPR values, in this work, a new Generalized Chirp-Like Precoding based UFMC (GCL-P-UFMC) system is proposed. The Monte-Carlo simulations of the proposed GCL-P-UFMC system indicate that the proposed system has low PAPR as compared to the conventional UFMC system and the Orthogonal Frequency Division Multiplexing (OFDM) system available in the literature. At a clip rate of 10-3, the proposed system gives on average 30 better PAPR results as compared to the conventional UFMC and OFDM systems. Â© 2019 IEEE.